2011
DOI: 10.1055/s-0031-1277230
|View full text |Cite
|
Sign up to set email alerts
|

A Ruptured Intraorbital Ophthalmic Artery Aneurysm, Associated with a Dural Arteriovenous Fistula: Combined Transarterial and Transvenous Endovascular Treatment

Abstract: Transvenous treatment of dAVFs is well feasible even with very far going catheterization, in this case to the origin of the basal vein of Rosenthal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Exophthalmos, visual impairment, and papilledema have been reported. Rupture of intraorbital OA aneurysms has also been reported (Kirsch and Henkes 2011;Meyerson and Lazar 1971). More than 50%, however, remain asymptomatic for a long time during their evolution.…”
Section: Discussionmentioning
confidence: 93%
“…Exophthalmos, visual impairment, and papilledema have been reported. Rupture of intraorbital OA aneurysms has also been reported (Kirsch and Henkes 2011;Meyerson and Lazar 1971). More than 50%, however, remain asymptomatic for a long time during their evolution.…”
Section: Discussionmentioning
confidence: 93%
“…A haemorrhagic presentation with rapid onset proptosis and visual loss is rare with only two reported cases 6 7. The most common presentations include visual loss, exophthalmos and headache.…”
Section: Discussionmentioning
confidence: 99%
“…They can also be asymptomatic and the rupture rate is thought to be low 3. There are currently 21 reports of intraorbital OA aneurysms 7–10. Eleven patients were noted to have concurrent vascular abnormalities including arteriovenous (AV) fistulae, AV malformations or cavernous malformation and other aneurysms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most unusual angiographic finding in our case was the spontaneous regression of the untreated right ophthalmic trunk aneurysm. The association between ophthalmic trunk aneurysms and other vascular malformations has been previously reported, although spontaneous aneurysm regression after the treatment of the vascular malformation was not detected in any of them(2,3).Kawaguchi et al(5) reported a case with a symptomatic (frontal headaches) anterior fossa DAVF fed by an OphA harboring an unruptured aneurysm of the intraorbital segment. The DAVF was surgically obliterated, although angiographic images or information about the state of the aneurysm during follow-up were not reported.…”
mentioning
confidence: 98%